Transcriptomic analysis of the root system of Platycodon grandiflorum in response to the fallen leaves of Acer truncatum - FENG Chaoqun; RUAN Kunfei; SHI Shaotong; LI Sen; CHENG Shaoying; LIU Zhonghua (Xibei zhiwu xuebao)
[Objective] The aim of this study was to explore the effect of Acer truncatum fallen leaves in Beijing on the accumulation of medicinal active ingredients of Platycodon grandiflorum and to reveal the molecular mechanism of active ingredient synthesis in P . grandiflorum roots through transcriptome sequencing. [Methods] We performed transcriptome sequencing using Illumina high throughput sequencing technology. Gene expression changes in the synthesis pathways of terpenes, flavonoids, and phenylpropanoid secondary metabolites were analyzed. [Results] A total of 15 727 SSR loci were detected. 753 differentially expressed genes (DEGs) were annotated into three major categories of the GO classification, and 314 DEGs were classified into 105 metabolic pathways in the KEGG classification. Compared with the control group, there were 17, 7, and 26 DEGs involved in the biosynthesis of terpenes, flavonoids, and phenylpropanoids, respectively. [Conclusion] We found that DEGs in the terpenes and phenylpropanoid synthesis pathways were mainly up-regulated, while DEGs in the flavonoid synthesis pathway were generally down-regulated. It is speculated that the synthesis of terpenes and phenylpropanoids is increased, while the synthesis of flavonoids is decreased. We obtained the transcriptome information of P . grandiflorum roots and preliminarily predicted the regulatory pathways for the synthesis of terpenes, flavonoids, and phenylpropanoids in P . grandiflorum .